Lithium-Substituted Tunnel/Spinel Heterostructured Cathode Material for High-Performance Sodium-Ion Batteries - Liang, Xinghui; Kim, Hun; Jung, Hun-Gi; Sun, Yang-Kook (WILEY-V C H VERLAG GMBH, 2021)
Sodium manganese oxides as promising cathode materials for sodium-ion batteries (SIBs) have attracted interest owing to their abundant resources and potential low cost. However, their practical application is hindered due to the manganese disproportionation associated with Mn3+, resulting in rapid capacity decline and poor rate capability. Herein, a Li-substituted, tunnel/spinel heterostructured cathode is successfully synthesized for addressing these limitations. The Li dopant acts as a pillar inhibiting unfavorable multiphase transformation, improving the structural reversibility, and sodium storage performance of the cathode. Meanwhile, the tunnel/spinel heterostructure provides 3D Na+ diffusion channels to effectively enhance the redox reaction kinetics. The optimized [Na0.396Li0.044][Mn0.97Li0.03]O-2 composite delivers an excellent rate performance with a reversible capacity of 97.0 mA h g(-1) at 15 C, corresponding to 82.5% of the capacity at 0.1 C, and a promising cycling stability over 1200 cycles with remarkable capacity retention of 81.0% at 10 C. Moreover, by combining with hard carbon anodes, the full cell demonstrates a high specific capacity and favorable cyclability. After 200 cycles, the cell provides 105.0 mA h g(-1) at 1 C, demonstrating the potential of the cathode for practical applications. This strategy might apply to other sodium-deficient cathode materials and inform their strategic design.
Keywords: HIGH-CAPACITY; HIGH-ENERGY; NA0.44MNO2; LI; NANOWIRES; STORAGE; CAPABILITY; INSERTION; NANORODS; LAYER